Bridging Regional Inequality in Indonesia: an Endogenous Growth and Structural Transformation Perspective - Gede Crisna Wijaya; Dewa Jati Primajana; Diah Pradnyadewi T.; I Komang Gede (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Regional development in Indonesia is still facing challenges such as regional inequality, disparities in the quality of human resources, and access to digital testing. This research aims to analyse strategic issues in regional development with a focus on GDP movement, HDI, and the digital divide. The approach taken is a literature review of reputable academic sources, reports from international organisations (UNDP, OECD, ADB), and empirical national data. To build the theoretical basis from this data collection, New Economic Geography is used as a grand theory, supplemented with the application of endogenous growth theory to clarify the role of innovation as human capital. The results of this study demonstrate that areas with better infrastructure, education, and digital resilience are able to grow more quickly and have a greater potential for better integration into the economic system; conversely, areas that are lagging in terms of infrastructure, education, and digital resilience will be pressured in their development. This disparity is felt more acutely post-pandemic. These findings underline the need for location-based development policies, strengthening regional governance systems, and more effective fiscal decentralisation policies, culminating in a more inclusive digital governance system. In conclusion, sustainable regional development can only be achieved through strategies that emphasise location-based development, enhancement of human resource quality, and the utilisation of technology in integrated economic development. Keywords: regional development, regional inequality, HDI, digital transformation